Comprehensive Genetic Characterization of a Spanish Brugada Syndrome Cohort. - Elisabet Selga; Oscar Campuzano; Mel Lina Pinsach-Abuin; Alexandra Pérez-Serra; Irene Mademont-Soler; Helena Riuró; Ferran Picó; Mònica Coll; Anna Iglesias; Sara Pagans; Georgia Sarquella-Brugada; Paola Berne; et al. (PLoS ONE, 2015)
Brugada syndrome (BrS) is a rare genetic cardiac arrhythmia that can lead to sudden cardiac death in patients with a structurally normal heart. Genetic variations in SCN5A can be identified in approximately 20-25% of BrS cases. The aim of our work was to determine the spectrum and prevalence of genetic variations in a Spanish cohort diagnosed with BrS.We directly sequenced fourteen genes reported to be associated with BrS in 55 unrelated patients clinically diagnosed. Our genetic screening allowed the identification of 61 genetic variants. Of them, 20 potentially pathogenic variations were found in 18 of the 55 patients (32.7% of the patients, 83.3% males). Nineteen of them were located in SCN5A, and had either been previously reported as pathogenic variations or had a potentially pathogenic effect. Regarding the sequencing of the minority genes, we discovered a potentially pathogenic variation in SCN2B that was described to alter sodium current, and one nonsense variant of unknown significance in RANGRF. In addition, we also identified 40 single nucleotide variations which were either synonymous variants (four of them had not been reported yet) or common genetic variants. We next performed MLPA analysis of SCN5A for the 37 patients without an identified genetic variation, and no major rearrangements were detected. Additionally, we show that being at the 30-50 years range or exhibiting symptoms are factors for an increased potentially pathogenic variation discovery yield.In summary, the present study is the first comprehensive genetic evaluation of 14 BrS-susceptibility genes and MLPA of SCN5A in a Spanish BrS cohort. The mean pathogenic variation discovery yield is higher than that described for other European BrS cohorts (32.7% vs 20-25%, respectively), and is even higher for patients in the 30-50 years age range.